PEMAHAMAN AKUNTANSI DASAR PADA USAHA MIKRO KECIL DAN MENENGAH DI DUSUN NGOROK DESA KOPANG REMBIGA - Baiq Qistinnisa; Aminy, Muhammad Habibullah; Dara Nida Utamie; Triana Lidona Aprilani (Nusantara Hasana Journal, 2025)
This study aims to evaluate the extent to which Micro, Small, and Medium Enterprises (MSMEs) in Ngorok Hamlet, Kopang Rembiga Village, Central Lombok Regency understand basic accounting. Although MSMEs have a crucial role in the local economy, many business actors in this area have not implemented accounting records in accordance with existing standards. In this study, a descriptive qualitative method was used by conducting in-depth interviews with five selected business actors. The research findings show that their understanding of basic accounting is still very limited, where most MSME actors do not understand or do not carry out financial records systematically. The factors that cause this include low levels of accounting literacy, non participation in training, and lack of resources. This study recommends that community-based training be held and the use of simple technology as a solution to improve the efficiency of financial management and business continuity through the application of basic accounting in accordance with the Financial Accounting Standards for Micro, Small, and Medium Entities (SAK EMKM).